La sistematización de prácticas educativas en el Colegio Jaime Hernando Garzón Forero de Bogotá como herramienta de difusión para la gestión del conocimiento - Gutiérrez Ortiz, Lina María (Universidad Pedagógica y Tecnológica de Colombia, 2023)
In the present research of the systematisation of the educational experiences of recovery and diffusion of these, carried out in the Alianza Educativa Organisation of Bogotá, aims to recover and interpret through a reflective critique. For this, it was proposed as an objective to reveal the reasons why the systematisation of educational experiences is not associated with knowledge management, as well as establishing the scope and limitations of systematising experiences. Within the organization, an innovation fair is held where teachers briefly systematize educational practices, unfortunately, all that work does not transcend the classroom, are not executed again or are not used in a long term period, this means that if the teacher quits the institution, those practices disappear and all the effort ends in just a mere presentation in front of a jury. In this way, these educational practices are strategies and powerful knowledge that should be identified, shared, disseminated in order to strengthen schools and expand their intellectual capital and value the teacher, in repercussion improving the learning processes. For instance, it is of utmost necessity to recover them and make them visible. The objective of organising the educational practices that are already systematised is that they can be extended within all schools under Alianza Educativa administration as solid foundations in knowledge management processes; this process was performed as follows:first of all, codes were created for the project formats and reference tables with the objectives, research project titles,references and findings. Second, two experts, two school administrators and three teachers were interviewed with the aim of knowing their perception on educational practices systematisation , their diffusion and knowledge management. The techniques used were documentary analysis, semi-structured interview and analysis matrix which helped to analyse the information so as to achieve a formative and reflective critique.